Biomarkers of inflammation in the context of acute illness among children 12–24 months of age living in the urban slums of Mumbai - Rajagopalan, Kripa; Huey, Samantha; Venkatramanan, Sudha; Udipi, Shobha; Thakker, Varsha; Thorat, Aparna (American Society for Nutrition, 2020)
To examine and compare the concentration of acute phase proteins, including nutritional and inflammation biomarkers, by morbidity status among children 12–24 months old living in urban slums of Mumbai.